1994
DOI: 10.1007/bf00150345
|View full text |Cite
|
Sign up to set email alerts
|

Vessel-diameter distribution in roots of grapevines (Vitis vinifera L. cv. Shiraz)

Abstract: The distribution frequency patterns of diameter of xylem vessels and percentage of total predicted axial conductances were studied in 190-day and 212-day-old main roots of grapevines (Vitis vinifera L. cv. Shiraz) grown under well-watered and stressed conditions. The protoxylem were the first to mature and were responsible for most of the theoretical conductance in root segments between the tip and 2.5 cm from the tip. Some large xylem vessels retained cross walls and protoplasm up to 22.5 cm from the tip. Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 15 publications
0
6
0
1
Order By: Relevance
“…Previous investigations have shown that xylem vessels under stress, when compared with control vessels, will decrease in diameter and will be distributed in different patterns about the stele of the plant (Mapfumo, Aspinall, and Hancock 1994). Furthermore, this pigeon pea study revealed that stress became more pronounced as the experiment progressed from 2 to 64 days.…”
Section: Discussionmentioning
confidence: 80%
“…Previous investigations have shown that xylem vessels under stress, when compared with control vessels, will decrease in diameter and will be distributed in different patterns about the stele of the plant (Mapfumo, Aspinall, and Hancock 1994). Furthermore, this pigeon pea study revealed that stress became more pronounced as the experiment progressed from 2 to 64 days.…”
Section: Discussionmentioning
confidence: 80%
“…6 provides a visual summary of steady‐state ion levels in the different cell types of salinized grapevine roots. Ten to 12 millimetre basipetal to the root tip the vascular tissue contains mainly protoxylem (Mapfumo, Aspinall & Hancock 1994) and therefore the contribution of this region of the root to Cl – accumulation in the shoot is unknown. The lack of data on the functionality of xylem in this region of the grapevine root limits the conclusions that can be made about the contributions that this region makes to the Cl – content of shoots.…”
Section: Discussionmentioning
confidence: 99%
“…The control of Cl – accumulation is still not fully understood although hypotheses have been proposed (Cram 1983). Our data show that cortical cells across the root have similar Cl – content, but the Cl – content for the hypodermis and the endodermis were lower than those of the cortex and pericycle.…”
Section: Discussionmentioning
confidence: 99%
“…6 provides a visual summary of steady-state ion levels in the different cell types of salinized grapevine roots. Ten to 12 millimetre basipetal to the root tip the vascular tissue contains mainly protoxylem (Mapfumo, Aspinall & Hancock 1994) and therefore the contribution of this region of the root to Claccumulation in the shoot is unknown. The lack of data on the functionality of xylem in this region of the grapevine root limits the conclusions that can be made about the contributions that this region makes to the Clcontent of shoots.…”
Section: Summary Of Ion Distribution Patterns In Grapevine Rootsmentioning
confidence: 99%